2019
DOI: 10.3390/f11010022
|View full text |Cite
|
Sign up to set email alerts
|

Soil pH and Organic Matter Content Affects European Ash (Fraxinus excelsior L.) Crown Defoliation and Its Impact on Understory Vegetation

Abstract: European ash (Fraxinus excelsior L.) dieback caused by the fungus Hymenoscyphus fraxineus (T. Kowalski) Baral, Queloz, and Hosoya has been affecting European forests since 1992. The disease drives severe crown defoliation, branch loss, and finally tree mortality in European ash. The environmental factors affecting the disease process are still not fully recognized. We hypothesized that the level of crown defoliation in ash, as well as its impact on understory vegetation, will differ along the pH gradient in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Other studies have indicated also that soil may indirectly affect ADB by the promotion of fungus inoculation because of high soil moisture and soil reaction variability [4,6,32]. Among the soil factors affecting the mortality rates of ash are soil pH, calcium carbonate content, high air humidity, and shallow groundwater table level [5,33]. These soil conditions occur in alder-ash forest chosen to collect ash saplings for our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have indicated also that soil may indirectly affect ADB by the promotion of fungus inoculation because of high soil moisture and soil reaction variability [4,6,32]. Among the soil factors affecting the mortality rates of ash are soil pH, calcium carbonate content, high air humidity, and shallow groundwater table level [5,33]. These soil conditions occur in alder-ash forest chosen to collect ash saplings for our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The observed results agree with previous studies showing that H . fraxineus induces changes in habitat structure and that these changes interact with plantation age (Erfmeier et al., 2019; Turczański et al, 2020). Due to leaf and branch loss, the tree canopy thinned and created gaps that were colonized by shrubs.…”
Section: Discussionmentioning
confidence: 99%
“…The lethal disease is thus often referred to as ash-dieback. Mortality opens tree canopies in forests, increasing light availability and promoting the growth of understorey vegetation (Turczański et al, 2020). Although the impact of H. fraxineus on the forest physical structure may superficially resemble impacts of other disturbance types (Heilmann-Clausen et al 2013;Swanson et al 2011), a mathematical model has indicated that the ash-dieback would lead to extinction cascades of many ash-associated species across several trophic levels (Hultberg et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations